Judaism and the Person with Intellectual Disability - Merrick, Joav (Journal of religion, disability & health, 2001)
The cornerstones of Judaism are the people (Am Israel), the land (Erez Israel) and the Written and Oral teachings (Torah Israel). Judaism is not only a religion, but a way of life. Not only for special events, like circumcision, bar mitzvah, weddings or funerals, but every minute of the life of a Jewish person. Judaism is not just an aspect of a Jew's life, but the totality of it. Torah operates all the time, covers every aspect of life and is unchangeable, unamendable and absolute. Torah is so deep spiritually that a lifetime is not enough to understand it fully. Rambam, a great scholar, said: “For one who gladdens the heart of these unfortunate is similar to the Divine, “as it says,” To revive the spirit of the lowly and to revive the heart of the contrite.” Jewish Law and scholars over time have stressed the need for education, acceptance and obligations towards persons with intellectual disability. This presentation will discuss the Jewish aspects of intellectual disability.